Influence of edaphic factors on the growth of a plantation of Pinus greggii Engelm. in Santiago de Anaya, Hidalgo, Mexico - Domínguez Calleros, Pedro Antonio; Díaz Vásquez, Manuel Antonio; Rodríguez Laguna, Rodrigo; Capulín Grande, Juan; Razo Zárate, Ramón (Instituto de Ecología, A.C., 2017)
The aim in this research was to evaluate survival and growth of a Pinus greggii plantation established since 2003, in a site (2.1 ha) with degraded soil and scarce precipitation. In particular, site soil characteristics and its influence on the development of the plantation were assessed. Vegetation coverage, natural regeneration and fuel load were also recorded. For this, nine circular sampling plots (1/10 ha) were measured in three random blocks according to the slope. Average survival was 91%, with better percentages in the middle and lower blocks of the plantation. Height, diameter and volume showed significant differences among blocks and subsites; larger values and increments were recorded in trees of the lower sites which are more fertile. In average, height was 9.4 m, diameter 14.4 cm and volume 60.2 m3 rta ha-1. In the upper portions of the land the lower vegetation cover was found (9.6 % of the soil), favoring the natural regeneration of plants typical in sites with high luminosity, like agaves, registering an average of 400 individuals per hectare. With respect to fuel material, this was found only in the inferior and middle subsites, the most abundant being the material with more than 5 cm in diameter (69.2 kg ha-1). Since this fuel is dispersed all around, it does not represent a threat of fire to the plantation. It is recommended to perform pre thinning and pruning to reduce competition among trees and incorporate organic matter to the soil in order to improve its conditions. These actions will reduce competition and increase the wood quality, as well as improve the edaphic conditions of the site by incorporating the plant material into the soil.